Pengaruh Emisi Karbon, Remitansi Tenaga Kerja dan Pengeluaran Pemerintah terhadap GDP per kapita negara anggota G20 - Achmad Thoriq Khautsar; Mike Triani (Media Riset Ekonomi Pembangunan (MedREP), 2026)
This study examines the effects of carbon emissions, labor remittances, and government spending on GDP per capita as an indicator of welfare in G20 countries during 2016–2023. The study employs panel data sourced from the World Development Indicators (WDI) and other international institutions. GDP per capita is treated as the dependent variable, while carbon emissions, labor remittances, and government spending are the independent variables. The analysis uses panel data regression with a Fixed Effect Model (FEM), selected based on the Chow and Hausman tests. The results indicate that carbon emissions have a negative and significant effect on GDP per capita, suggesting that environmental externalities reduce welfare levels. Labor remittances show a positive but statistically insignificant effect, implying a limited contribution to aggregate economic welfare. Meanwhile, government spending has a negative and significant effect, indicating inefficiencies in public expenditure management that hinder its role in improving welfare. Overall, the findings highlight that welfare in G20 countries is influenced by environmental, external income, and fiscal factors. Therefore, improving welfare requires policies focused on sustainable environmental management, more productive use of remittances, and enhanced efficiency in government spending.